2015
DOI: 10.1002/ijc.29713
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor responses by combined GITR activation and sunitinib in metastatic renal cell carcinoma

Abstract: Sunitinib, a multitargeted tyrosine kinase inhibitor, is the frontline therapy for renal and gastrointestinal cancers. In view of its well-documented proapoptotic and immunoadjuvant properties, we speculate that combination of Sunitinib and immunotherapy would provide a synergistic antitumor effect. Here, we report that a remarkably synergistic antitumor responses elicited by the combined treatment of Sunitinib and an agonistic antibody against glucocorticoid-induced TNFR related protein (GITR) in a model of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 48 publications
(94 reference statements)
2
21
0
Order By: Relevance
“…The combination of antiangiogenic therapy and immunotherapy has been explored in a variety of pre-clinical models (Table 1) and forms the basis for a number of current clinical trials (Table 2). Much of the pre-clinical evidence relates to adoptive cell transfer and vaccination strategies, in combination with a wide variety of antiangiogenic therapies including VEGF-A blockade (97, 98, 111), VEGFR-2 blockade (100, 101), ligand traps (99, 112), receptor tyrosine kinase inhibitors (106, 107, 114, 115), irradiation (166), and angiostatic peptides (102, 103, 105, 113). For example, Shrimali et al demonstrated enhanced tumor infiltration, decreased tumor size, and improved survival when adoptive T cell transfer was combined with treatment with an anti-mouse VEGF-A antibody in a mouse model of melanoma (97).…”
Section: Implications For Treatment Strategiesmentioning
confidence: 99%
“…The combination of antiangiogenic therapy and immunotherapy has been explored in a variety of pre-clinical models (Table 1) and forms the basis for a number of current clinical trials (Table 2). Much of the pre-clinical evidence relates to adoptive cell transfer and vaccination strategies, in combination with a wide variety of antiangiogenic therapies including VEGF-A blockade (97, 98, 111), VEGFR-2 blockade (100, 101), ligand traps (99, 112), receptor tyrosine kinase inhibitors (106, 107, 114, 115), irradiation (166), and angiostatic peptides (102, 103, 105, 113). For example, Shrimali et al demonstrated enhanced tumor infiltration, decreased tumor size, and improved survival when adoptive T cell transfer was combined with treatment with an anti-mouse VEGF-A antibody in a mouse model of melanoma (97).…”
Section: Implications For Treatment Strategiesmentioning
confidence: 99%
“…70 Over the last decennia, anti-angiogenic drugs targeting the receptor-ligand interactions by monoclonal antibodies like bevacizumab or tyrosine kinase inhibitors were widely applied in clinical practice. Both act as tumor suppressors by promoting TAMs with an antitumor phenotype [71][72][73][74][75] or by decreasing monocyte recruitment. [76][77][78][79][80] This beneficial effect is partially compromised by activation of HIF-1α pathways that lead to an angiogenic counterresponse.…”
Section: Tams and Anti-angiogenic Therapymentioning
confidence: 99%
“…75 Tyrosine kinase inhibitors have more effects on immune cells. Erlotinib reportedly induces apoptosis of monocytic cell lines in vitro.…”
Section: Neurooncologymentioning
confidence: 99%
“…Recent study showed that sunitinib in combination with α-GITR could induce the significant infiltration of immune cells in tumor-metastatic liver, where the cell proliferation, activation and effector of CD8 + T cells and/or NK cells were extremely prominent [6]. The sequence of administration of immune treatment and targeted therapy is important.…”
Section: Discussionmentioning
confidence: 99%